The magnetic ground state of Ba(Fe1/2Sn1/2)O3-δ: A potential giant dielectric material for technological applications - Kumar A.; Sahu G. (My University, 2025)
Ba(Fe1/2Sn1/2)O3-δ (BFSO) is a potential environmental friendly compound for miniaturization of electronic devices as it exhibits giant dielectric constant at room temperature. However, its magnetic ground state is not settled. We present here comprehensive investigation of the as-sintered and oxygen-annealed BFSO samples using x-ray diffraction, dielectric, x-ray photoelectron spectroscopy (XPS), dc magnetization (M(T, H, t)) and specific heat measurements. Both samples crystallize in a cubic Pm-3m symmetry. At room temperature, both samples show a giant dielectric constant of the order of ε' ∼104 and two low-temperature dielectric relaxations resulting from polaron-hoping and Maxwell-Wagner effect, respectively. The temperature-dependent dc magnetization and specific heat measurements on as-sintered and oxygen-annealed BFSO samples confirm the absence of long-range ordered antiferromagnetic transition at TN ∼55 K. Further, both samples show history-dependent irreversibility of zero-field cooled warming (ZFCW) and field cooled warming (FCW) M(T) curves at the irreversibility temperature (Tirr ∼18 K) with a peak in the ZFCW M(T) curve at the spin-glass freezing temperature Tf ∼16 K. In addition, the FCW M(T) curve of both samples show plateauing over a small temperature range before it starts increasing below Tf, a characteristic typically observed in cluster/spin-glass systems. The presence of long-time magnetic relaxation and aging effect in both samples further support the spin-glass behavior. We also discussed the impact of oxygen vacancies on the physical and magnetic properties and possible origin of the glassy ground state in BFSO. © 2023 Elsevier B.V.